2022
DOI: 10.3390/foods11121774
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Sensory and Bioactive Properties of Yogurt with the Introduction of Tartary Buckwheat

Abstract: The incorporation of cereals in yogurt has recently gained increasing consumer approval, for its high nutritional value and health benefits, all over the world. Following this emerging trend, Tartary buckwheat (TB) was supplemented into yogurt as a natural functional ingredient in order to develop a yogurt with enhanced product characteristics and consumer acceptability. The impact of TB addition on physicochemical properties (pH, acidity, apparent viscosity, etc.) and the viability of lactic acid bacteria in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In Tartary buckwheat and in its milling fractions, there are, besides the main phenolic compounds, many other secondary metabolites as volatile aromatic compounds, which may appear as well in Tartary buckwheat food products. They are in low concentrations, so it is not expected that they would have any major bioactive impact of some importance, at least such was not reported according to the knowledge of the present authors [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 58%
“…In Tartary buckwheat and in its milling fractions, there are, besides the main phenolic compounds, many other secondary metabolites as volatile aromatic compounds, which may appear as well in Tartary buckwheat food products. They are in low concentrations, so it is not expected that they would have any major bioactive impact of some importance, at least such was not reported according to the knowledge of the present authors [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 58%
“…It led to a decrease in the numbers of bacteria, yeasts and molds due to the presence of various compounds such as polyphenolics and monoterpenes that affect the growth of disease-causing microorganisms, especially gram-positive ones. Ye et al 38 have confirmed that the most important factor and the main determinant of choosing yogurt by consumers is flavor, especially acceptance and preference, especially acetaldehyde. It imparts a wonderful taste and is an attractive nutritional component that is considered the most important in yogurt.…”
Section: Resultsmentioning
confidence: 96%
“…In control, stirring or shaking suddenly causes water to leave the protein network and increases yogurt syneresis (Marand et al ., 2020). The buckwheat had filled empty pores of yogurt protein network and prevented whey from leaking (Ye et al ., 2022). The results investigated that yogurt microstructure containing exopolysaccharides, which caused syneresis reduction and filling of the yogurt microstructure (Marand et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%